A Casting Mould for Rapid Tube Hydroforming Prototyping - Kochański, Andrzej; Sadłowska, Hanna (Journal of Casting & Materials Engineering, 2020)
In recent years, hydroforming has clearly expanded its range of industrial applications due to the growing interest in products which combine high strength with low weight. A current limitation of this technology was its economically justified production volume since the costs of producing tools eliminates the possibility of using hydroforming technology in prototype and single part production. The paper presents a freshly patented solution that allows for single part hydroforming. The new technology combines traditional hydroforming machines with a new approach to tool production. The new rapid die is made quickly and cheaply. The use of materials known from the production of foundry moulds causes the die to deform during hydroforming, but it is a controlled deformation. Thanks to the use of numerical modelling, the deformation of the mould cavity is predicted and taken into account at the design stage. The article presents important issues that need to be considered in the design of this innovative process.